Arsitektur Perilaku untuk Kualitas Hidup Mahasiswa: Desain Hunian Komunal Responsif Perilaku di Sleman, Yogyakarta - Irma Noviani Susanti; Suparno Suparno (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Behavioral Architecture for Student Quality of Life:Responsive Communal Housing Design in Sleman, YogyakartaThe need for behaviorally responsive communal housing in Sleman is urgent to address conventional design issues (density, conflict). This study aims to develop a student housing design framework based on Behavioral Architecture. Using a descriptive qualitative method with Behavior Mapping and empirical study, behavioral data was analyzed for applicable design guidelines. The result is an innovative Design Framework, including the Extended Core Corridor Plan concept and semi-private unit zoning, which functionally addresses behavioral needs. The Novelty lies in the synthesis of local empirical behavioral data (Sleman) converted into an integrated design model to enhance Student Quality of Life.